Microstructure and properties of aluminum AA6061-T6 to copper (Cu)-T2 joints by cold metal transfer joining technology. Issue 18 (30th August 2016) - Cai, Z.P.; Ai, B.Q.; Cao, R.; Lin, Q.; Chen, J.H.
Abstract: Abstract : Recently, cold metal transfer (CMT) process has been successfully applied to weld dissimilar metals. In this paper, two different aluminum alloy AA6061-T6 and pure copper T2 lapped joints were performed by CMT with AA4043 aluminum alloy wire as the filler metal. Results indicated that sound lapped joints between aluminum alloy AA6061-T6 and pure copper T2 could be performed by CMT technology. The joint was composed of Al–Al welding joint and Al–Cu brazing joint. The Al–Al welding joint was formed between the Al weld metal and the Al base metal, and the weld metal in Al–Al welding joint was composed of α-Al solid solution, α-Al, and CuAl eutectic phase. Al–Cu brazing joint was formed between the Al weld metal and the local molten Cu base metal, and composed of three copper-weld metal interfaces with a large amount of intermetallic compounds (IMCs), i.e., CuAl2, CuAl. The optimum strength of two joints could reach up to 1.23 kN and 1.56 kN, respectively, which was mainly due to the differences of the size of Cu/Al IMCs and stress condition. In addition, the distribution of microhardness and fracture surface of two joints were observed and analyzed in detail.